Effect of Special Allocation Funds (DAK), Capital Expenditures, and Investment on Economic Growth in the Sulawesi Region - Fera Nur Ariyani Ibrahim; Irawati Abdul (Jambura Equilibrium Journal, 2019)
This study aims to analyze the effect of Special Allocation Funds, Capital Expenditures and Investment on Economic growth in the Sulawesi region. The data used are secondary data obtained from Simreg Bappenas and the Central Statistics Agency during 2007-2016. The unit of analysis is 6 provinces in the Sulawesi region. This study uses a panel data regression model with the Random Effect Model (REM) method. The results of this study indicate that, (i) the Special Allocation Fund has a negative and significant effect on economic growth in the Sulawesi region. (ii) Capital expenditure shows a positive and significant influence on economic growth in the Sulawesi region. (iii) Investment shows a positive and significant influence on economic growth in the Sulawesi region.